2018
DOI: 10.21873/anticanres.12828
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Levels of the Angiogenic Cytokine Endocan Are Elevated in Patients with Multiple Myeloma

Abstract: The plasma levels of endocan can non-invasively differentiate patients newly diagnosed with MM from those with MGUS and should therefore be evaluated prospectively as a potential diagnostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…12,[16][17][18][19][20] High levels of endocan have also been detected at in many types of cancer, and it may show cancer activation and differentiate benign and malignant disease. [21][22][23][24] COVID-19 can be associated with micro and/or macro emboli and progresses with vascular inflammation. [25][26][27] In this context, our study was based on the hypothesis that endocan levels, which are a specific marker for vascular endothelial cells, will be elevated levels in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[16][17][18][19][20] High levels of endocan have also been detected at in many types of cancer, and it may show cancer activation and differentiate benign and malignant disease. [21][22][23][24] COVID-19 can be associated with micro and/or macro emboli and progresses with vascular inflammation. [25][26][27] In this context, our study was based on the hypothesis that endocan levels, which are a specific marker for vascular endothelial cells, will be elevated levels in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…12,1620 High levels of endocan have also been detected at in many types of cancer, and it may show cancer activation and differentiate benign and malignant disease. 2124…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endocan values have found to be significantly increased in sepsis, type 2 diabetes mellitus, systemic lupus erythematosus, renal insufficiency, oncologic diseases, Behçet disease, psoriasis vulgaris, and epilepsy in adults. [41][42][43][44][45][46][47][48][49] In pediatric populations, recent studies reported high serum endocan levels in patients with necrotizing enterocolitis and juvenile idiopathic arthritis in the neonatal period. 50,51 But to the best of our knowledge, there is no study in a pediatric population assessing the risk of atherosclerosis in obese patients using endocan and cIMT.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations have consistently confirmed the abnormal expression of ESM1 in the blood or tumor tissues of patients with diverse cancers. Notably, elevated ESM1 levels have been observed in the circulatory systems of patients diagnosed with endometrial, cervical, renal, breast and lung cancer, multiple myeloma and hepatocellular carcinoma (19,(86)(87)(88)(89)(90). Furthermore, upregulated ESM1 expression has been detected in tumor samples collected from patients with pancreatic neuroendocrine tumors and glioblastoma (91,92).…”
Section: Value Of Esm1 As a Prognostic And Predictive Indicator Of Ca...mentioning
confidence: 99%